A Modified Bilaminar Technique with the Use of a Fibrin-Fibronectin System for a Single Gingival Recession: A Case Report with a Follow-Up of 3 Years. (30th September 2020) - Perelli, Michele; Arduino, Paolo Giacomo; Semenza, Mario; Abundo, Roberto; Sarmiento, Hector
Abstract : This case report described a modified bilaminar technique for treating a single gingival recession. Patient presented a gingival recession in a maxillary canine. Tooth was in a buccally prominent position and soft keratinized tissue apical to the recession was reduced but still present. A split-full-split thickness trapezoidal flap was designed. Root's surface was prepared with curettes. Epithelial-connective tissue graft was harvested from the palate with reduced dimension. After deepithelialization, the graft was placed with a fibrin-fibronectin system at the maximum root coverage level, and the flap coronally advanced and sutured. At 3-year follow-up control, the free gingival margin was still stable at the postsurgery position, with a thicker biotype corresponding to the grafted area, with no probing and a suitable aesthetic result.